Ezh2 and Runx1 mutations collaborate to initiate lympho-myeloid leukemia in early thymic progenitors - Booth, CAG; Barkas, N; Neo, WH; Boukarabila, H; Soilleux, EJ; Giotopoulos, G; Farnoud, N; Giustacchini, A; Ashley, N; Carrelha, J; Jamieson, L; Atkinson, D; et al. (Elsevier, 2018)
Lympho-myeloid restricted early thymic progenitors (ETPs) are postulated to be the cell of origin for ETP leukemias, a therapy-resistant leukemia associated with frequent co-occurrence of EZH2 and RUNX1 inactivating mutations, and constitutively activating signaling pathway mutations. In a mouse model, we demonstrate that Ezh2 and Runx1 inactivation targeted to early lymphoid progenitors causes a marked expansion of pre-leukemic ETPs, showing transcriptional signatures characteristic of ETP leukemia. Addition of a RAS-signaling pathway mutation (Flt3-ITD) results in an aggressive leukemia co-expressing myeloid and lymphoid genes, which can be established and propagated in vivo by the expanded ETPs. Both mouse and human ETP leukemias show sensitivity to BET inhibition in vitro and in vivo, which reverses aberrant gene expression induced by Ezh2 inactivation.